Emotional perception of individuals with Autism Spectrum disorder through Machine learning and smart watch (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper proposes a system that analyses the requirements of people with autism spectrumdisorder and to alter the caretaker to acknowledge the present feeling in them to ease sureactivity problems. This may be achieved through sensible devices. The smartwatch systemmonitors the feeling through the galvanic skin response and graphical record, that measures theelectrical physical phenomenon of the skin and electrical signals from the scalp of the brain. Thesignals area unit digitized. Then acceptable emotions area unit classified through the SupportVector Machine algorithmic program. The intensity and therefore the form of feeling area unitflashed on the caretaker's communication device